2002
DOI: 10.17221/4470-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Fruit weight, firmness and soluble solids content during ripening of Karešova cv. sweet cherry

Abstract: Changes in fruit weight, firmness and soluble solids content during the ripening period of Karešova cv. including relationships between these characteristics were studied in 1998-2001. These years differed from each other in the amount and distribution of rainfall and in the course of temperatures. The length of ripening period fluctuated from 14 to 21 days. An increase in average fruit weight during the ripening period was 0.1 g per day. The actual increase in fruit weight was in a close correlation with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…However, the mean fruit firmness was lower during the rainfall year (2017) like that obtained during the drought year (2015). It has been reported that fruit firmness decrease with rainfall increasing [17]. These findings are in accordance with those obtained in the present study for the year 2015 and 2016.…”
Section: Genotype and Year Effects On Physical Fruit Traitssupporting
confidence: 94%
See 1 more Smart Citation
“…However, the mean fruit firmness was lower during the rainfall year (2017) like that obtained during the drought year (2015). It has been reported that fruit firmness decrease with rainfall increasing [17]. These findings are in accordance with those obtained in the present study for the year 2015 and 2016.…”
Section: Genotype and Year Effects On Physical Fruit Traitssupporting
confidence: 94%
“…In sweet cherry, the final fruit size and weight is related to the cell length than to the numbers of cells [15]. Thus, climatic conditions and supply resources limitations affected more final cherry size during cell enlargement (stage III of fruit development) than cell division (during stage I) [16,17]. The data of rainfall registered in 2016 showed that the amount of precipitation during the May and June (corresponding to the stage III of fruit development) was higher than that registered in 2015 and 2017 during the same period (Table 3).…”
Section: Genotype and Year Effects On Physical Fruit Traitsmentioning
confidence: 99%
“…However, some authors (Drake andElfving 2002, Serrano et al 2009) suggest delaying the harvest time, which could enhance consumer appeal, increase fruit value, improve the quality of fruits (i.e. fruit size and SSC), and increase the yield (at the average rate of about 2% per day) (Blažková et al 2002). Our study showed that the rootstocks significantly affected the quality features (fruit firmness, SSC, TA) of 'Regina' sweet cherry fruit at harvest (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Sample S-3 (34.1 °Bx) contained significantly high soluble solid contents as compared to other samples (Table 2). Blažková et al (2002) also found positive correlations between the weight (size) of fruits and soluble solid contents.…”
Section: Hardness and Moisture And Soluble Solid Contentsmentioning
confidence: 70%